Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Sabun Cair dari Minyak Jelantah untuk Meningkatkan Ekonomi Masyarakat Desa Gayam Kecamatan Gondang Wetan Kabupaten Pasuruan - Rif’an Fauzi (Social Science Academic, 2025)
This research aims to empower the people of Gayam Village, Gondang Wetan District, Pasuruan Regency through training in making liquid soap from used cooking oil as an effort to improve the economy of the local community. The research method used is a qualitative approach with direct training techniques and assistance in liquid soap production. The results of the study show that this training has succeeded in improving the knowledge and skills of the community in processing used cooking oil into liquid soap products that have selling value. The positive impact of this training is an increase in the community's source of income so as to improve the economic welfare of families and reduce used cooking oil waste that has the potential to pollute the environment. This study recommends the development of similar training on an ongoing basis to improve the economic capabilities and environmental awareness of village communities